FAKTOR FAKTOR PENYEBAB KEMATIAN MATERNAL DI KABUPATEN TASIKMALAYA TAHUN 2015 - widiyanti, ranti (Jurnal Ilmu Kesehatan Immanuel, 2019)
ABSTRACT   The case of maternal mortality is still high in Tasikmalaya regency. In 2014, it is recorded as many as 31 cases and increase in 2015 as many as 55 cases. The local government has made various efforts to reduce the case of maternal mortality, but the results are still not optimal. Knowing the factors of the case is one of the preventive effort to reduce it. The purpose of the research was to analyze the factors of maternal mortality. The research used analytic descriptive method with quantitative approach. The type of the research is analytical research in the form of observation of the studied subject with secondary data from Verbal Autopsy Maternal data with Cross-sectional study design in 55 cases of maternal mortality in 2015. The results showed, the factors that play a role in maternal mortality in Tasikmalaya regency are age, parity, low education, low socio economic, birth attendants, birth complications, delays in the referral process and the handling of the referral process. The decrease of maternal mortality rate is started from the awareness of mother, husband, family, health workers and policy makers of the importance of maternal and infant survival. Maternal mortality is a problem that can not be resolved until today even though the various policies have been made in order to reduce maternal deaths. Keywords: factors that play a role, maternal mortality